Nexus Between Capital Market Development and Economic Growth: Evidence from Nepal (Quest Journal of Management and Social Sciences, 2025)
Background: The global scenario reveals mixed impact of capital market development on economic growth. While advanced economies benefit from efficient capital markets through savings mobilization, resource allocation, and risk diversification, relationship remains unclear in developing economies. In many such economies, capital markets have shown limited impact on real sector despite their potential to bridge investment gaps. This ambiguity has drawn scholarly attention to ascertain the relationship between capital market development and economic growth.Methodology: The Autoregressive Distributed Lag (ARDL) bounds test explains the long-run cointegration among the variables since variables under study have mixed order of integration. An error correction model is used to explain the short-run relationship while Granger-causality test with lag of 2 is applied to check causality among the variables under study.Results: The empirical study finds a weak long-run cointegration between capital mobilisation through the primary market (CMP) and economic growth, while market capitalisation (MC) shows no significant long-run impact. CPI positively affects economic growth, but remittance inflow has a negative expected sign. In the short run, both CMP and one-year lag of MC significantly influence economic growth. Additionally, a unidirectional causal relationship exists from CMP to real GDP, whereas no causality is found between MC and real GDP.Conclusion: The capital market has a mixed influence on Nepal's economy. While the primary market positively contributes to GDP in short and long run, the secondary market shows a negative effect. A one-year lag in market capitalisation positively affects GDP in short run. Resource mobilisation through diverse financial products and sectoral investment should be encouraged to boost economic growth.